Comparison between a VET-related search query in an Internet search engine and via a subject-specific information resource : paper presented at the European Conference on Educational Research (ECER), Helsinki, Finland, 25 August 2010 - Linten, Markus [Verfasser]; Toth, Bernadette [Verfasser] (Bundesinstitut für Berufsbildung, 2010)
"The paper focuses on the opportunities for successful scholarly research through effective use of the Internet. A systematic approach necessary for the research of specialist scientific information is then demonstrated. In conclusion, a selection of useful information resources for the subject field is introduced. A comparison between a search query related to Vocational Education and Training (VET) in an Internet search engine with a query in special online portals and databases will be drawn. A comparison will be made with the query "Implementation of National Qualifications Framework in Austria and in Germany in the course of the Implementation of the European Qualification Framework" for the purpose of pointing out the advantage of using subject-specific information resources. The subject-specific information resources "ReferNet-Portal", the German Literature Database on VET-topics "LDBB" and CEDEFOPs "European Literature database VET-Bib" will be presented. Finally, this paper also emphasises the necessity of information literacy. It will be argued that information professionals should actively promote their work in order not to become redundant." (BIBB-Doku)
Keywords: S 5.2 Wissensmanagement; I 1.5 Internationale Organisationen & Institutionen; G 2.2 Informations- / Wissensgesellschaft; L 4.2.4 Expertennetzwerke / Wissensplattformen; Informationsgewinnung; Berufsbildung; Suchmaschine; Datenbank; Recherche; ReferNet